2010
DOI: 10.1128/aem.00117-10
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Putative Cell Surface Polysaccharide Biosynthesis Gene SO3177 in Shewanella oneidensis MR-1 Enhances Adhesion to Electrodes and Current Generation in Microbial Fuel Cells

Abstract: A microbial fuel cell (MFC) was inoculated with a random transposon insertion mutant library of Shewanella oneidensis MR-1 and operated with lactate as the sole fuel to select for mutants that preferentially grew in it. Agar plate cultivation of the resultant MFC enrichment culture detected an increased number of colonies exhibiting rough morphology. One such isolate, strain 4A, generated 50% more current in an MFC than wild-type MR-1. Determination of the transposon insertion site in strain 4A followed by del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 42 publications
5
107
0
1
Order By: Relevance
“…Comparative analyses of the abilities of several different Shewanella strains to adhere to hematite (␣-Fe 2 O 3 ) revealed that strains with more hydrophobic and electronegative cell surfaces exhibited better adhesion (42). In addition, Shewanella cells with a more hydrophobic and electronegative surface have been shown to enhance not only cell adhesion to graphite electrodes but also cell-cell adhesion as evidenced by strong autoaggregation (25). The hyperadherent phenotype of CP2-1-S1 suggests that its cell surface physicochemical properties, such as charge and hydrophobicity, might have been altered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative analyses of the abilities of several different Shewanella strains to adhere to hematite (␣-Fe 2 O 3 ) revealed that strains with more hydrophobic and electronegative cell surfaces exhibited better adhesion (42). In addition, Shewanella cells with a more hydrophobic and electronegative surface have been shown to enhance not only cell adhesion to graphite electrodes but also cell-cell adhesion as evidenced by strong autoaggregation (25). The hyperadherent phenotype of CP2-1-S1 suggests that its cell surface physicochemical properties, such as charge and hydrophobicity, might have been altered.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that cell surface charges and hydrophobicity play an important role in cell adhesion to biotic and abiotic surfaces (25,41,42). Hydrophobic interactions have been shown to be an important factor controlling the adhesion of Shewanella cells to amorphous Fe(III) oxide (41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension was centrifuged and the cells were then washed with DM before use in electrochemical experiments. Mutant strains of MR-1 lacking complete genes for MtrC and SO3177 were previously constructed by allele replacement using a two-step homologous recombination method (28,37). The growth procedures for the two mutant strains were the same as described for the WT MR-1 strain.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the involvement of heme molecules in the OM c-Cyts proteins of MR-1 cells in the observed EET reaction between bacteria and electrodes, we examined mutant strains with inframe deletions of the genes encoding MtrA, MtrB, MtrC, OmcA, and CymA. Each mutant was constructed by allele replacement using a two-step homologous recombination method, as previously reported (Saltikov & Newman 2003;Kouzuma et al, 2010).…”
Section: In-frame Deletion Mutants Of Om C-cytsmentioning
confidence: 99%